Power sharing in community-engaged research with Syrian refugees in Lebanon: Using community engagement to shape intervention fit to context - R. Nakkash; M. Fares; M. Tleis; S. Mugharbil; M. Antaby; H. Al Masri; L. Ghandour; F. Al Halabi; Y. Najjar; B. Louis; R. Afifi (SSM - Mental Health)
Our study assesses the community-engaged research approach (CEnR) followed during the planning phase for a randomized controlled trial designed to assess how young adult Syrian refugees living in the Bekaa region of Lebanon implementing PM+ with adults in their community will be impacted themselves. We aim to describe the community-engaged research process implemented in our study, and the impact of community engagement on the process of adaptation of the intervention, and the design of the study. Methods: Community-engaged research (CEnR) was used to adapt this intervention to the context of the young adult Syrian refugee community in Lebanon by forming a community alliance committee (CAC). Twelve members from the Syrian refugee community in the Bekaa, Lebanon with different professional and socio-demographic characteristics who have lived experience or expertise related to mental health, education, health more generally, or young adults were invited to join a community alliance committee. Thematic analysis was conducted for two sources of data: (1) minutes of the CAC meetings; (2) in-depth interviews conducted with five CAC members. Findings demonstrate that community-engaged research increases rigor and relevance of the intervention and influenced outcomes, process, and context measures. Suggested modifications made by the CAC members enhanced the social and cultural relevance of the intervention, the measurement tools, and the study's approach. Conclusion: Our results showed that a CEnR process contributes to building trust with the community, creating a safe space for everyone to share their inputs, and when integrating those inputs into the adaptation of the intervention, results in a more contextualized intervention.